Logística de transportes e comércio internacional: os fluxos das exportações e das importações de mercadorias no norte de Minas Gerais - Pereira, Luiz Andrei Gonçalves (2015)
The general objective of this thesis was to analyze the spatial interactions between the northern region of Minas Gerais state and international markets, considering the territorial configuration of the exporting and importing sectors, transports and media of the bonded areas responsible for the flow of goods in the period 2001 to 2012. The survey was implemented in three stages. At first, focused literature review to discuss the concepts and themes geared to the logistics of transport; in the second stage, the studies were focused on the collection and analysis of data from secondary sources drawn from governmental and non-Brazilian and foreign government; the third stage, occurred collecting empirical data on primary sources through semi-structured interviews, applied together with the representatives of the logistics industry and foreign trade of exporting and importing companies in the north of Minas Gerais. In this research, the adopted methodological resources that culminated in the thesis were discussed. The concepts of technical networks, logistics and transport were discussed to explain the process of organization and spatial distribution of flows of goods and services in geographic space. In international trade, were characterized flows of exports and imports of goods and services, with an emphasis on business transactions in the world, Brazilian, mining and North mining scales. The transport logistics network and its modalities were discussed trying to explain the spatial interactions of exported goods flows and imported by Northern companies of Minas Gerais, customs facilities and arrangements for international transport. It is concluded that the international trade flows represented by exports and imports are centered in the national transportation network in customs areas and in international transport. In international transport, maritime prevails for low value-added goods, and the air, which concentrates the high value-added goods. As for exported and imported by the US-mining region goods, circulate predominantly in the country by road.